Potential of four Turkish isolates of entomopathogenic nematodes against three major stored products insect pests. (September 2019) - Yuksel, Ebubekir; Canhilal, Ramazan; Imren, Mustafa
Abstract: The insecticidal effect of native entomopathogenic nematode (EPN) isolates ( Steinernema feltiae UTP-5 isolate, Heterorhabditis bacteriophora UMK-7 isolate, S. feltiae DDKY-11 isolate and H. bacteriophora AVB-15 isolate) recovered from the Cappadocia Region of Turkey were investigated on the adults of S. granarius and R. dominica and the larvae of E. kuehniella at different temperatures (15 °C, 20 °C and 25 °C) and concentrations (250, 500 and 1000 IJs/adult for S. granarius and R. dominica ; 10, 50 and 100 IJs/larvae for E. kuehniella ) under controlled conditions. Insect mortality was recorded after 4th, 6th and 8th day of exposure time for S. granarius and R. dominica, and 2nd and 4th day for E. kuehniella . The results showed that the efficacy of the isolates at 25 °C was generally higher than the ones at 15 °C and 20 °C. Steinernema feltiae DDKB-17 isolate caused the highest mortality (86%) against S. granarius adults at all temperatures tested. The virulence of the tested isolates on R. dominica adults did not exceed 44% at all temperatures and concentrations tested. UMK-7 and AVB-15 isolates were the most virulent isolates against E. kuehniella larvae with a mortality rate of 100%. Based on the results obtained from the laboratory tests, it appeared that the isolates tested have a good potential for the management of S. granarius, R. dominica and E. kuehniella . Highlights: The mortality rates caused by EPN isolates tested varied according to the host species used, nematode concentration, temperature, and both EPN species and isolates. S. feltiae DKB-17 isolate was the most effective against the Sitophilus granarius adults among the other isolates ( Heterorhabditis bacteriophora UMK-7 isolate; Steinernema feltiae UTP-5 isolate; H. bacteriophora AVB-15 isolate). Rhyzopertha dominica adults showed the least susceptibility to nematode infection.